Modified graphite electrode for antibiotic production wastewater treatment as well as preparation method and application of modified graphite electrode

By forming graphene sheets and spinel nanoparticles on the surface of the graphite electrode, the problem of easy corrosion and poor stability in the electrochemical advanced oxidation reaction is solved, and the effect of efficient degradation of antibiotic production wastewater in extreme acid and alkali environments is achieved.

CN119873969APending Publication Date: 2025-04-25SHENYANG INST OF APPL ECOLOGY CHINESE ACAD OF SCI

Patent Information

Application Number
CN202510215131.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Graphite electrodes are easily corrosive in electrochemical advanced oxidation reactions, have poor stability, and have low degradation efficiency in extreme acid and alkali environments, making it difficult to meet the treatment needs of antibiotic production wastewater.

Method used

The graphene sheet layer was generated on the surface of the graphite electrode by electrochemical modification, and spinel nanoparticles were generated on the graphene sheet layer by in-situ crystallization method, and finally calcined to form a modified graphite electrode.

Benefits of technology

It significantly improves the stability of graphite electrodes and the resistance of extreme acid and alkali environments, improves the activation efficiency of peroxide oxidants, and achieves efficient mineralization and degradation of antibiotics and their coexisting organic pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873969A_ABST
    Figure CN119873969A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of pharmaceutical wastewater treatment, and particularly relates to a modified graphite electrode for antibiotic production wastewater treatment, a preparation method of the modified graphite electrode and application of the modified graphite electrode in an electrochemical advanced oxidation treatment system. The preparation method comprises the following steps: carrying out electrochemical modification on a graphite electrode, generating spinel nanoparticles on a graphene sheet layer through an in-situ crystallization method, and calcining the modified graphite electrode. After the graphite electrode is modified, the resistance to a strong acidic water environment in an electrochemical advanced oxidation reaction process can be remarkably improved, and the spinel nanoparticles can effectively activate a peroxide oxidant; rich oxygen-containing functional groups in a graphene sheet layer can activate an oxidizing agent through a redox reaction and promote redox circulation of metal elements in a spinel structure. The problem of corrosion when the graphite electrode is applied to an electrochemical advanced oxidation reaction can be solved, and the electrode stability, the oxidant utilization efficiency and the antibiotic mineralization efficiency are jointly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of pharmaceutical wastewater treatment, and in particular relates to a modified graphite electrode for treating antibiotic production wastewater, a preparation method thereof, and an application thereof in an electrochemical advanced oxidation treatment system. Background Art

[0002] Carbon materials have good electrical conductivity, high chemical stability and excellent electrocatalytic activity for a variety of redox reactions, so they have been widely studied as electrocatalysts and catalyst carriers. Among them, graphite is one of the commonly used electrode materials for electrochemical advanced oxidation reactions. Graphite electrodes are widely used in electro-Fenton reactions, electrocatalytic persulfate oxidation reactions, and electrically enhanced heterogeneous catalytic oxidation reactions, etc., to carry out research and practice on the degradation of antibiotics in wastewater. Although graphite electrodes have good electrochemical properties, their thermodynamic instability under oxidation conditions makes them extremely susceptible to corrosion, thereby reducing the service life of the electrode and the reaction efficiency. Compared with the standard hydrogen electrode potential (SHE), the standard potential for carbon oxidation is 0.207V, that is, the electrochemical corrosion of carbon is thermodynamically favorable above this potential. In addition, O2 and reactive oxygen species (ROS) present in the water electrochemical environment will cause carbon surface reactions, which is also the main cause of carbon corrosion. Severe carbon oxidation will destroy the integrity of carbon and cause the structural collapse of the carbon electrode. Carbon electrodes are easily oxidized at high anodic potentials, but this is also an inevitable requirement for the degradation of organic pollutants by the anodic oxidation process of electrochemical advanced oxidation reactions.

[0003] In order to improve the adaptability of graphite electrodes to dye wastewater with different pH values, patent CN105948180B discloses a modification method, in which the surface of the graphite electrode is polished with sandpaper and then immersed in NaOH solution and hydrochloric acid solution in turn, rinsed and dried, and then immersed in Co2O3-NH2-MCM-41 powder (MCM-41 and 3-aminopropyltrimethoxysilane are mixed in n-hexane, condensed at room temperature, filtered, rinsed and dried to obtain NH2-MCM-41 powder, and then prepared into a mixed aqueous solution with Co2O3 powder, and reacted in a reactor at 105°C for 10 hours) and polyethylene oxide mixed aqueous solution for ultrasonic treatment for 20 to 40 minutes. The specific surface area, catalytic activity and oxidizability of the modified graphite electrode were significantly improved, but the dye degradation efficiency under acidic (pH=3, 82.81%) and alkaline (pH=9, 92.37%) reaction conditions was still lower than that under neutral conditions (pH=7, 99.52%).

[0004] CN113479994A discloses a method for preparing a graphene-magnetite conductive skeleton electrode, wherein graphene-magnetite-Geobacter sulfurreducens bacteria (mixed with a soluble iron salt solution of pH=6.5-7.5, a culture medium and graphene, and prepared by adding Geobacter sulfurreducens bacteria under a nitrogen atmosphere) is mixed with a Nafion solution to form a suspension, which is then coated on the surface of a graphite rod electrode. The method is based on the principle of microbial electrochemistry and can simultaneously achieve the treatment of petrochemical wastewater and energy recovery. However, in addition to the slow microbial membrane enrichment process (10-15 days), the reaction process also requires the addition of a microbial culture medium (1g / L sodium acetate, 12.5ml / L metal solution, 5ml / L vitamin solution, etc.) to the petrochemical wastewater, and the acid-base resistance, long-term effect and stability of the modified graphite electrode are not clear.

[0005] CN101697323A discloses an electrochemically modified graphite electrode, which is electrochemically oxidized (1-300 mA / cm2) in an aqueous electrolyte solution with ion conductivity (H2SO4 or HClO4 aqueous solution). 2 ) and electrochemical reduction (-1~-300mA / cm 2 ) after the cycle treatment between the graphite body, an activation layer is generated in situ on the surface of the graphite body, which can be used as an electrode material for electrochemical capacitors, and has performance characteristics such as high conductivity, high power density and high-speed charging and discharging. However, whether the electrochemically modified electrode can be used for the electrochemical treatment of wastewater, the invention patent does not give specific examples and application effects.

[0006] CN108862483B discloses a method for preparing an electrode for electrocatalytic degradation of organic pollutants, using graphite paper as an anode, a platinum electrode as a cathode, and a mixed aqueous solution of sodium nitrate (0.1-0.5M), potassium permanganate (1-10mM) and sulfuric acid (0.5-1.0M) as an electrolyte, and preparing the target electrode by electrochemical oxidation method (1-3V, 10-30min). The electrode can achieve efficient electrocatalytic degradation of rhodamine B in a wide pH range (pH=3-11), but the application range of graphite paper (50-300μm) as an electrode is narrow, and the current density used for electrocatalytic degradation is high (10-50mA / cm 2 ), high energy consumption, and the concentration of organic pollutants that can be treated is relatively low (20-40 mg / L).

[0007] Electrochemical advanced oxidation is an environmentally friendly water treatment technology with the advantages of mild conditions, easy control, and automated operation. In recent years, it has been proven in scientific research and practice that it can effectively treat antibiotic-containing wastewater. However, there are currently few anode materials that can be used in engineering practice, which are mainly limited by cost, electrode life and stability, catalytic activity and energy consumption. Therefore, how to improve the stability of graphite electrodes and avoid their oxidative corrosion, improve their adaptability to extreme acid and alkaline environments, and efficiently mineralize and degrade organic pollutants under low anode potential conditions to reduce energy consumption are key issues that need to be solved to promote the practical application of electrochemical advanced oxidation technology in the field of difficult-to-degrade wastewater treatment. Summary of the invention

[0008] The purpose of the present invention is to promote the application of electrochemical advanced oxidation technology in the field of pharmaceutical wastewater treatment, and to propose a modified graphite electrode for antibiotic production wastewater treatment and a preparation method thereof and its application in an electrochemical advanced oxidation treatment system.

[0009] In order to achieve the above object, the technical solution adopted by the present invention is:

[0010] A method for preparing a modified graphite electrode for treating antibiotic production wastewater comprises electrochemically modifying the graphite electrode, then generating spinel nanoparticles on a graphene sheet by an in-situ crystallization method, and then calcining the modified graphite electrode.

[0011] Specifically:

[0012] (1) Electrochemical modification of graphite electrodes, wherein the graphite electrodes are subjected to anodic oxidation and cathodic reduction treatments in a three-electrode reaction system as a cycle;

[0013] (2) Repeating the above cycle treatment repeatedly to obtain an electrochemically modified graphite electrode;

[0014] (3) rinsing the electrochemically modified graphite electrode with ultrapure water and drying it;

[0015] (4) immersing the electrochemically modified graphite electrode in a metal salt solution to perform an in-situ crystallization reaction of spinel nanoparticles;

[0016] (5) After the reaction is completed, the electrode is calcined to obtain the final modified graphite electrode.

[0017] In the three-electrode reaction system, the graphite electrode is subjected to anodization treatment and cathode reduction treatment in sequence; wherein, the anodization treatment is to apply a current of 100 to 300 mA for a treatment time of 60 to 600 seconds, and the graphite electrode is cleaned with ultrapure water after the treatment; the cathode reduction treatment is to apply a current of -50 to -300 mA for a treatment time of 30 to 240 seconds, and the graphite electrode is cleaned with ultrapure water after the treatment.

[0018] In the three-electrode reaction system, the graphite electrode is the working electrode, the reference electrode is the silver / silver chloride electrode or the saturated calomel electrode, the auxiliary electrode is the platinum sheet or the platinum disk electrode; the electrolyte is a 1-5M HNO3 solution, a 1-3M H2SO4 solution, or a 1-3M HClO4 solution.

[0019] The above cycle is repeated 2-10 times.

[0020] The electrochemically modified graphite electrode is rinsed with ultrapure water until the pH of the rinse solution is close to neutral, and then vacuum dried at 60° C. for 6 to 12 hours.

[0021] The electrochemically modified electrode is immersed in a metal salt solution, immersed (0.5-5h) under slow speed (30-100rpm), constant temperature (25-100°C) stirring conditions, and in-situ crystallization is performed to form spinel nanoparticles. The formed spinel nanoparticles have a loading ratio of 10-500mg / cm 2 ; Wherein, the element composition of the spinel nanoparticles is A x B 3-x O4 (A = Ni, Co, Cu, Fe, Mn; B = Co, Fe, Mn; x = 1, 2), the amount of addition is based on the metal element and its x B 3-x The metal salt solution is prepared by mixing a metal salt mixture with a boiling alkali solution to achieve a system pH value of 12.

[0022] The metal salt mixed liquid is two or more of Ni(NO3)2·6H2O, Zn(NO3)2·6H2O, CuSO4, Fe(NO3)3·9H2O / FeCl3·6H2O, Co(NO3)3·6H2O / CoCl2·6H2O, MnCl2, and KMnO4; the boiling alkali solution is a NaOH solution of NaBH4 (2.0 g NaBH4 is dissolved in 0.1 M NaOH solution).

[0023] The calcination is to calcine the electrode at 300° C. to 600° C., then rinse with anhydrous ethanol and distilled water in sequence, and vacuum dry at 60° C. for 6 to 12 hours.

[0024] A modified graphite electrode for treating wastewater from antibiotic production is prepared according to the method to obtain a modified graphite electrode with a flaky surface for treating wastewater from antibiotic production.

[0025] An application of the modified graphite electrode for treating antibiotic production wastewater, and an application of the modified graphite electrode in treating antibiotic production wastewater in an electrochemical advanced oxidation treatment system.

[0026] Furthermore, the modified graphite electrode is used in an electrochemical advanced oxidation treatment system as an anode for the treatment of antibiotic production wastewater.

[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0028] Graphite electrodes are susceptible to electrochemical oxidation corrosion, have poor stability, and have a high surface oxidation state, which makes them only able to adsorb · OH forms advanced oxides (chemically adsorbed active oxygen) as intermediates to participate in the transformation and selective oxidation of organic matter (complete mineralization of organic matter cannot be achieved). The present invention proposes that graphene sheets are first generated on the surface of a graphite electrode by electrochemical modification, and then spinel nanoparticles are in situ grown on the surface of the generated graphene sheets by an in situ crystallization method. This can effectively avoid electrochemical corrosion of the graphite electrode, improve tolerance to extreme acid and alkali environments, reduce the potential and current density of the anodic oxidation reaction, and improve the activation efficiency and utilization efficiency of the electrode for peroxide oxidants, thereby achieving efficient mineralization and degradation of antibiotics and their coexisting organic pollutants. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A schematic diagram of the preparation process of the modified graphite electrode provided in an embodiment of the present invention;

[0030] Figure 2 A schematic diagram of an electrochemical advanced oxidation treatment system for antibiotic production wastewater provided by an embodiment of the present invention;

[0031] Figure 3 The treatment effect of antibiotic production wastewater when the modified graphite electrode (CoFe2O4 is generated in situ on the surface) provided by the embodiment of the present invention is used as the anode of the electrochemical advanced oxidation treatment system;

[0032] Figure 4 The treatment effect of antibiotic production wastewater when the modified graphite electrode (CuFe2O4 is generated in situ on the surface) provided by the embodiment of the present invention is used as the anode of the electrochemical advanced oxidation treatment system;

[0033] Figure 5 The treatment effect of antibiotic production wastewater when the modified graphite electrode (Cu2MnO4 is generated in situ on the surface) provided by the embodiment of the present invention is used as the anode of the electrochemical advanced oxidation treatment system;

[0034] Figure 6 The treatment effect of antibiotic production wastewater when the modified graphite electrode (Fe2MnO4 is generated in situ on the surface) provided by the embodiment of the present invention is used as the anode of the electrochemical advanced oxidation treatment system;

[0035] Figure 7The antibiotic degradation efficiency and metal ion leaching of the modified graphite electrode provided in the embodiment of the present invention after ten consecutive reactions, (a) surface-grown CoFe2O4 modified graphite electrode, (b) surface-grown CuFe2O4 modified graphite electrode, (c) surface-grown Cu2MnO4 modified graphite electrode, (d) surface-grown Fe2MnO4 modified graphite electrode;

[0036] Figure 8 The treatment effect of antibiotic production wastewater when the unmodified graphite electrode provided by the embodiment of the present invention is used as the anode of the electrochemical advanced oxidation treatment system;

[0037] Fig. 9 The present invention provides an electrochemically modified graphite electrode provided in an embodiment of the present invention for treating antibiotic production wastewater when used as an anode in an electrochemical advanced oxidation treatment system. DETAILED DESCRIPTION

[0038] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0039] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0040] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0041] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0042] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0043] The modified electrode of the present invention is electrochemically modified in a three-electrode reaction system, with a graphite electrode as the working electrode, and graphene oxide and reduced graphene oxide sheets are generated in situ on the surface of the graphite electrode through anodic oxidation and cathode reduction, and then spinel nanoparticles are generated on the graphene sheets through an in situ crystallization method, and finally the electrode is calcined. After the graphite electrode is modified, its resistance to the strongly acidic water environment of the electrochemical advanced oxidation reaction process can be significantly improved, the spinel nanoparticles can effectively activate the peroxide oxidant, and the rich oxygen-containing functional groups of the graphene sheets can activate the oxidant through redox reactions and promote the redox cycle of metal elements in the spinel structure. The present invention can solve the corrosion problem of graphite electrodes when applied to electrochemical advanced oxidation reactions, and achieve the joint improvement of electrode stability, oxidant utilization efficiency and antibiotic mineralization efficiency.

[0044] The equipment, materials and reagents used in the following examples of the present invention are all commercially available.

[0045] In the following embodiments of the present invention, HNO3, H2SO4, HClO4, Zn(NO3)2·6H2O / ZnCl2·6H2, Cu(NO3)2·3H2O / CuSO4, Fe(NO3)3·9H2O / FeCl3·6H2O, Co(NO3)3·6H2O / CoCl2·6H2O, MnCl2, KMnO4, NaOH, anhydrous ethanol, etc. are all analytically pure reagents; the graphite electrode is a commercially available material customized and processed in appropriate sizes; the silver / silver chloride electrode, saturated calomel electrode, platinum sheet electrode, and platinum disk electrode are commercially available products customized and processed in appropriate sizes.

[0046] The following examples serve as further illustrations of the technical solutions of the present invention.

[0047] Example 1

[0048] Schematic diagram of the preparation process of modified graphite electrode Figure 1 As shown. First, the graphite electrode was electrochemically modified. In the three-electrode reaction system, a cylindrical graphite electrode (1 cm in diameter and 30 cm in length) was used as the working electrode, a platinum sheet was used as the auxiliary electrode (counter electrode, 10 cm in length*5 cm in width*0.3 mm in thickness), a saturated calomel electrode was used as the reference electrode, and the electrolyte was HNO3 solution (3M). The anodic oxidation treatment applied a current of 300 mA for 300 s, and the graphite electrode was cleaned with ultrapure water after treatment; the cathode reduction treatment applied a current of -150 mA for 120 s, and the graphite electrode was cleaned with ultrapure water after treatment; after 4 cycles of anodic oxidation and cathode reduction treatment, an electrochemically modified graphite electrode was obtained.

[0049] The electrochemically modified graphite electrode was immersed in a metal salt solution to perform an in-situ crystallization reaction of spinel nanoparticles. Taking the in-situ generation of CoFe2O4 on the surface of the electrochemically modified graphite electrode as an example, a mixed solution of CoCl2·6H2O (100 ml, 0.02 M) and FeCl3·6H2O (100 ml, 0.04 M) was first prepared (stored at 60°C), and then the mixed solution was added to a boiling NaOH solution (the boiling alkali solution was a NaOH solution of NaBH4 (2.0 g NaBH4 dissolved in 0.1 M NaOH solution, 800mL, pH=12), and then immerse the electrochemically modified graphite electrode in the above metal salt mixture, and immerse and react for 1h under slow (50rpm) and constant temperature (85℃) stirring conditions. After the reaction, the electrode was calcined at 400℃, and then rinsed with anhydrous ethanol and distilled water in turn, and vacuum dried at 60℃ for 8h to obtain the final modified graphite electrode, with a CoFe2O4 loading ratio of about 74.7mg / cm 2 For the in-situ generation of CuFe2O4 on the surface of electrochemically modified graphite electrode, CoCl2·6H2O (100ml, 1M) was replaced with Cu(NO3)2·3H2O (100ml, 1M) and prepared by the same method as above. The CuFe2O4 loading ratio was about 76.2mg / cm 2 .

[0050] For the in-situ generation of Cu2MnO4 on the surface of electrochemically modified graphite electrode, amorphous MnO2 nanoparticle precursor was first prepared. 100 mL of MnCl2 aqueous solution (0.3 M) and 50 mL of KMnO4 aqueous solution (0.4 M, pH = 12) were mixed at room temperature and stirred at 100 rpm until the precipitation was complete. The precipitate was filtered and washed repeatedly with ultrapure water, dried at 60 ° C for 6 h, and then ground to 200 mesh. 1.74 g of the above-mentioned MnO2 nanoparticles and 3.82 g of CuSO4 were added to 100 mL of ultrapure water to prepare a mixed solution, and then the mixed solution was added to an excess of NaBH solution (the boiling alkali solution was a NaOH solution of NaBH4 (2.0 g of NaBH4 was dissolved in a 0.1 M NaOH solution, 900 mL, so that the system pH = 12), and the electrochemically modified graphite electrode was immersed in the above-mentioned mixed solution, and immersed for 1 hour under slow (50 rpm) and constant temperature (25°C) stirring conditions. After the reaction was completed, the electrode was calcined at 400°C, and then rinsed with anhydrous ethanol and distilled water in turn, and vacuum dried at 60°C for 8 hours to obtain the final modified graphite electrode, and the Cu2MnO4 loading ratio was about 78.4 mg / cm 2 .

[0051] For the in-situ generation of Fe2MnO4 on the surface of electrochemically modified graphite electrode, CuSO4 (3.82 g) was replaced by FeCl3·6H2O (10.8 g) and prepared by the same method as above. The Fe2MnO4 loading ratio was about 73.5 mg / cm 2 .

[0052] Example 2

[0053] Treatment of antibiotic production wastewater in electrochemical advanced oxidation treatment system ( Figure 2 ), mainly including a glass fiber reinforced plastic column reactor (20 cm in diameter, 25 cm in height, and a volume of about 8 L), a PVC sealing cover (with reserved electrode holes, an oxidant injection port, a wastewater injection port, and a drain port), an adjustable constant current DC power supply (maximum output current 10 A), an anode (modified graphite electrode, 1 cm in diameter, 30 cm in length), a titanium cathode (1 cm in diameter, 30 cm in length), a wastewater storage tank (100 L), an oxidant storage tank (100 L), a drain storage tank (100 L), a peristaltic pump, etc. The anode (the surface in-situ generated CoFe2O4 modified graphite electrode prepared in the above embodiment) and the cathode, the oxidant (permonosulfate) injection pipe, the wastewater injection pipe, and the drain pipe are inserted into the reactor through the reserved hole of the sealing cover, and antibiotic production wastewater (about 6.3 L, the liquid level is about 20 cm, and the physical and chemical properties are shown in Table 1) is injected into the reactor through the peristaltic pump, and the DC power supply (output current 0.2 A, electrode current density about 3 mA / cm 2 ), reaction time 120min.

[0054] Table 1 Physical and chemical properties of actual penicillin production wastewater (unit: mg / L)

[0055] index pH <![CDATA[COD Cr ]]> <![CDATA[BOD5]]> <![CDATA[NH3-N]]> <![CDATA[NO3 - -N]]> TN penicillin Numeric 6.0 6000 1100 22 265 450 5.1

[0056] Penicillin was determined by high performance liquid chromatography (Shimadzu LC-20AT) equipped with an Agilent ZORBAXSB Aq (4.6×250mm, 5μm) column, the mobile phase was 0.1% formic acid and acetonitrile (35:65, v:v), the flow rate was 0.8mL / min, the injection volume was 20μL, and the detection wavelength was 210nm.

[0057] The toxicity changes before and after wastewater treatment were characterized by antibacterial activity tests on Gram-positive bacteria (Staphylococcus aureus, S. aureus). The bacteria were inoculated in LB medium and cultured in a constant temperature shaking incubator at 37°C for 12 hours. The treated water (1 mL) and the bacterial solution (0.2 mL) that had reached the culture time were added to fresh LB medium. After culturing for 24 hours under the above culture conditions, the absorbance of the culture solution was tested at a wavelength of 450nm using an ultraviolet spectrophotometer. At the same time, a control experiment was set up, that is, the treatment group with only sterilized water added. Bacterial growth inhibition rate (G r )Calculation formula:

[0058]

[0059] Among them, A0 is the absorbance test value of the control group, A t is the absorbance test value of the treatment group.

[0060] The results show that ( Figure 3 ), after the reaction, the penicillin concentration in the wastewater decreased from the initial 5.1 mg / L to 0 mg / L, and the removal efficiency reached 100%; the electrochemical advanced oxidation reaction can effectively remove COD in wastewater Cr (residual concentration 348mg / L, removal rate 94.2%), BOD5 (residual concentration 156mg / L, removal rate 86.8%), NH3-N (residual concentration 3.9mg / L, removal rate 82.3%), NO3 - -N (residual concentration 36.8mg / L, removal rate 86.1%), TN (residual concentration 93.6mg / L, removal rate 79.2%). At the same time, the biodegradability of wastewater was significantly improved, BOD5 / COD Cr The value increased from the initial 0.18 to 0.45. In addition, the bacterial inhibition rate of the treated wastewater decreased from the initial 78% to 0.1%, almost completely eliminating the bacterial inhibition of the wastewater.

[0061] Example 3

[0062] The reactor and reaction conditions used were the same as those in Example 2, except that the anode used a surface-modified graphite electrode prepared in the above example to generate CuFe2O4 in situ. Figure 4 ), after the reaction, the penicillin concentration in the wastewater decreased from the initial 5.1 mg / L to 0 mg / L, and the removal efficiency reached 100%; the electrocatalytic oxidation reaction can effectively remove COD in the wastewater Cr (residual concentration 258mg / L, removal rate 95.7%), BOD5 (residual concentration 106mg / L, removal rate 90.4%), NH3-N (residual concentration 2.7mg / L, removal rate 87.7%), NO3 --N (residual concentration 31.4mg / L, removal rate 88.2%), TN (residual concentration 81.9mg / L, removal rate 81.8%). At the same time, the biodegradability of wastewater was significantly improved, BOD5 / COD Cr The value increased from the initial 0.18 to 0.41. In addition, the bacterial inhibition rate of the treated wastewater decreased from the initial 78% to 0, completely eliminating the biological activity inhibition of the wastewater.

[0063] Example 4

[0064] The reactor and reaction conditions used are the same as those in Example 2, except that the anode uses a surface-modified graphite electrode prepared in the above example to generate Cu2MnO4 in situ. Figure 5 ), after the reaction, the penicillin concentration in the wastewater decreased from the initial 5.1 mg / L to 0 mg / L, and the removal efficiency reached 100%; the electrocatalytic oxidation reaction can effectively remove COD in the wastewater Cr (residual concentration 247mg / L, removal rate 95.9%), BOD5 (residual concentration 118mg / L, removal rate 89.3%), NH3-N (residual concentration 3.1mg / L, removal rate 85.9%), NO3 - -N (residual concentration 28.9 mg / L, removal rate 89.1%), TN (residual concentration 87.2 mg / L, removal rate 80.7%). At the same time, the biodegradability of wastewater was significantly improved, BOD5 / COD Cr The value increased from the initial 0.18 to 0.48. In addition, the bacterial inhibition rate of the treated wastewater decreased from the initial 78% to 0, completely eliminating the biological activity inhibition of the wastewater.

[0065] Example 5

[0066] The reactor and reaction conditions used are the same as those in Example 2, except that the anode uses a surface-modified graphite electrode prepared in the above example to generate Fe2MnO4 in situ. Figure 6 ), after the reaction, the penicillin concentration in the wastewater decreased from the initial 5.1 mg / L to 0 mg / L, and the removal efficiency reached 100%; the electrocatalytic oxidation reaction can effectively remove COD in the wastewater Cr (residual concentration 385mg / L, removal rate 93.6%), BOD5 (residual concentration 157mg / L, removal rate 85.7%), NH3-N (residual concentration 4.6mg / L, removal rate 79.0%), NO3 - -N (residual concentration 43.6mg / L, removal rate 83.5%), TN (residual concentration 103.7mg / L, removal rate 76.9%). At the same time, the biodegradability of wastewater was significantly improved, BOD5 / COD CrThe value increased from the initial 0.18 to 0.42. In addition, the bacterial inhibition rate of the treated wastewater decreased from the initial 78% to 0, completely eliminating the biological activity inhibition of the wastewater.

[0067] Example 6

[0068] The antibiotic degradation efficiency and metal ion leaching conditions of different modified graphite electrodes subjected to ten consecutive reactions are shown in the following table. Figure 7 As shown. The results show that the degradation efficiency of penicillin in the electrochemical advanced oxidation treatment system constructed based on different modified graphite electrodes is still higher than 95% after ten reactions (1200min), which confirms the effectiveness of the electrode for long-term use. The main reason for the reduction of penicillin oxidation degradation efficiency of the modified graphite electrode is the adsorption of penicillin and its degradation products on the electrode surface, and the catalytic activity can be restored after re-calcination. The amount of metal ion leaching: Co≤0.24mg / L, Fe≤0.1mg / L in the reaction system of the surface-grown CoFe2O4 modified graphite electrode; Cu≤0.15mg / L, Fe≤0.14mg / L in the reaction system of the surface-grown CuFe2O4 modified graphite electrode; Cu≤0.27mg / L, Mn≤0.07mg / L in the reaction system of the surface-grown Cu2MnO4 modified graphite electrode; Fe≤0.17mg / L, Mn≤0.08mg / L in the reaction system of the surface-grown Fe2MnO4 modified graphite electrode. All of them are lower than the standard limit requirements of different metal elements in the "Surface Water Environmental Quality Standard" (GB3838-2002) (Co: 1.0 mg / L, Fe: 0.3 mg / L, Cu (Class I ≤ 0.01 mg / L, Class II ≤ 1 mg / L), Mn: 0.1 mg / L), among which Cu meets the limit requirements of Class II surface water environmental quality standards, confirming the stability of the modified graphite electrode.

[0069] Comparative Example 1

[0070] The reactor and reaction conditions used were the same as those in Example 2, except that a common graphite electrode was used as the anode. Figure 8 ), after the reaction, the penicillin concentration in the wastewater decreased from the initial 5.1 mg / L to 3.3 mg / L, and the removal efficiency was only 35.3%; COD Cr (residual concentration 4380mg / L, removal rate 27.0%), BOD5 (residual concentration 832mg / L, removal rate 24.4%), NH3-N (residual concentration 15.9mg / L, removal rate 27.7%), NO3 - -N (residual concentration 184.1mg / L, removal rate 30.5%), TN (residual concentration 317.4mg / L, removal rate 29.5%) removal rates were both low. At the same time, the biodegradability of the wastewater was not significantly improved, BOD5 / COD CrThe value changed from the initial 0.18 to 0.19. In addition, the bacterial inhibition rate of the treated wastewater decreased from the initial 78% to 61%, and there was still a strong biological activity inhibition effect.

[0071] Comparative Example 2

[0072] The reactor and reaction conditions used were the same as those in Example 2 to prepare an electrochemically modified graphite electrode, that is, an electrochemically modified graphite electrode after the cathode and anode treatments were performed in accordance with Example 1. The results showed that ( Fig. 9 ), after the reaction, the penicillin concentration in the wastewater decreased from the initial 5.1 mg / L to 2.1 mg / L, with a removal efficiency of 58.8%; COD Cr (residual concentration 2370mg / L, removal rate 60.5%), BOD5 (residual concentration 568mg / L, removal rate 48.4%), NH3-N (residual concentration 10.7mg / L, removal rate 51.4%), NO3 - -N (residual concentration 118.2 mg / L, removal rate 55.4%), TN (residual concentration 210.7 mg / L, removal rate 53.2%) removal rates were both low. At the same time, the biodegradability of the wastewater was slightly improved, BOD5 / COD Cr The value changed from the initial 0.18 to 0.24. In addition, the bacterial inhibition rate of the treated wastewater decreased from the initial 78% to 47%, and there was still a strong biological activity inhibition effect.

[0073] In summary, when the modified graphite electrode prepared by the present invention is used as the anode of the electrochemical advanced oxidation treatment system, it can achieve the complete degradation of residual antibiotics in the antibiotic production wastewater and the simultaneous and efficient removal of other coexisting water pollutants, significantly improve the biodegradability of the production wastewater and almost or completely eliminate its biological activity inhibition effect, the electrode has good stability and high catalytic activity retention, and can achieve long-term and efficient use.

Claims

1. A method for preparing a modified graphite electrode for treating wastewater from antibiotic production, characterized in that: The graphite electrode is electrochemically modified, and then spinel nanoparticles are generated on the graphene sheet by an in-situ crystallization method. The modified graphite electrode is calcined.

2. The method for preparing a modified graphite electrode for treating antibiotic production wastewater according to claim 1, characterized in that: (1) Electrochemical modification of graphite electrodes, wherein the graphite electrodes are subjected to anodic oxidation and cathodic reduction treatments in a three-electrode reaction system as a cycle; (2) Repeating the above cycle treatment repeatedly to obtain an electrochemically modified graphite electrode; (3) rinsing the electrochemically modified graphite electrode with ultrapure water and drying it; (4) immersing the electrochemically modified graphite electrode in a metal salt solution to perform an in-situ crystallization reaction of spinel nanoparticles; (5) After the reaction is completed, the electrode is calcined to obtain the final modified graphite electrode.

3. The method for preparing a modified graphite electrode for treating antibiotic production wastewater according to claim 2, characterized in that: In the three-electrode reaction system, the graphite electrode is subjected to anodization treatment and cathode reduction treatment in sequence; wherein, the anodization treatment is to apply a current of 100 to 300 mA for a treatment time of 60 to 600 seconds, and the graphite electrode is cleaned with ultrapure water after the treatment; the cathode reduction treatment is to apply a current of -50 to -300 mA for a treatment time of 30 to 240 seconds, and the graphite electrode is cleaned with ultrapure water after the treatment.

4. The method for preparing a modified graphite electrode for treating antibiotic production wastewater according to claim 2 or 3, characterized in that: In the three-electrode reaction system, the graphite electrode is the working electrode, the reference electrode is the silver / silver chloride electrode or the saturated calomel electrode, the auxiliary electrode is the platinum sheet or the platinum disk electrode; the electrolyte is a 1-5M HNO3 solution, a 1-3M H2SO4 solution or a 1-3M HClO4 solution.

5. The method for preparing a modified graphite electrode for treating antibiotic production wastewater according to claim 2, characterized in that: The electrochemically modified graphite electrode is rinsed with ultrapure water until the pH of the rinse solution is close to neutral, and then vacuum dried at 60° C. for 6 to 12 hours.

6. The method for preparing a modified graphite electrode for treating antibiotic production wastewater according to claim 2, characterized in that: The electrochemically modified electrode is immersed in a metal salt solution and immersed (0.5 to 5 h) under slow speed (30 to 100 rpm) and constant temperature (25 to 100 ° C) stirring conditions to form spinel nanoparticles in situ crystallization. The load ratio of the formed spinel nanoparticles is 10 to 500 mg / cm 2 ; Wherein, the element composition of the spinel nanoparticles is A x B 3-x O4 (A = Ni, Co, Cu, Fe, Mn; B = Co, Fe, Mn; x = 1, 2), the amount of addition is based on the metal element and its x B 3-x The metal salt solution is prepared by mixing a metal salt mixture with a boiling alkali solution to achieve a system pH value of 12.

7. The method for preparing a modified graphite electrode for treating antibiotic production wastewater according to claim 6, characterized in that: The metal salt mixed liquid is two or more of Ni(NO3)2·6H2O, Zn(NO3)2·6H2O, CuSO4, Fe(NO3)3·9H2O / FeCl3·6H2O, Co(NO3)3·6H2O / CoCl2·6H2O, MnCl2, and KMnO4; the boiling alkali solution is a NaOH solution of NaBH4 (2.0 g NaBH4 is dissolved in 0.1 M NaOH solution).

8. The method for preparing a modified graphite electrode for treating antibiotic production wastewater according to claim 2, characterized in that: The calcination is to calcine the electrode at 300° C. to 600° C., then rinse with anhydrous ethanol and distilled water in sequence, and vacuum dry at 60° C. for 6 to 12 hours.

9. A modified graphite electrode for treating antibiotic production wastewater according to claim 1, characterized in that: The modified graphite electrode with a scaly surface prepared by the method according to claim 1 is used for treating wastewater from antibiotic production.

10. An application of the modified graphite electrode for treating antibiotic production wastewater according to claim 9, characterized in that: The modified graphite electrode is used in an electrochemical advanced oxidation treatment system to treat antibiotic production wastewater.

Citation Information

Patent Citations

  • Electrochemically modified graphite electrode

    CN101697323A

  • Preparation method and application of copper-iron bimetal / graphite felt composite electrode derived from MOF-74 precursor

    CN116332292A

Cited By

  • Preparation method and application of antibiotic electrocatalytic degradation electrode

    CN120553826A